A BOTANICAL INVENTORY OF FOREST ON KARSTIC LIMESTONE AND METAMORPHIC SUBSTRATE IN THE CHIQUIBUL FOREST, BELIZE, WITH FOCUS ON WOODY TAXA - Baden, H. M.; Särkinen, T.; Conde, D. A.; Matthews, A. C.; Vandrot, H.; Chicas, S.; Pennil, C.; Bayly, W. D. R.; Chance, R.; Bridgewater, S. G. M.; Harris, D. J. (Edinburgh Journal of Botany, 2015)
The Chiquibul Forest Reserve and National Park in Belize is a priority conservation area within the ‘Maya Forest’ in Central America. Although taxonomic data are essential for the development of conservation plans in the region, there is limited knowledge of the existing species in the area. Here we present a botanical species list of mostly woody taxa based on voucher specimens, with particular focus on the Raspaculo watershed in the eastern part of the National Park. Within the Raspaculo watershed, a comparison is made between 0.1 ha of valley floor and 0.1 ha of hilltop vegetation, sampling trees, shrubs, palms and lianas ≥2.5 cm diameter at breast height. Additionally, a 1 ha plot was established in the Upper Raspaculo watershed. Our study shows 38 new species records for the region, and important additions to the flora of Belize. New records were recorded from forests on both metamorphic and karstic substrate, including previously overlooked hilltop forest elements. Quantitative assessment of vegetation across elevation zones shows distinct elements dominating on valley floors and hilltops. Our results show that the Chiquibul contains at least 58% of Belize’s threatened plant species, and represent a source of information for the management and conservation of the area.